The Implementation of Edpuzzle in Teaching English for Pharmacists at ITEKES Bali - I Putu Agus Endra Susanta (ITScience (Information Technology and Science), 2024)
Edpuzzle is an interactive video-based learning platform increasingly utilized in various educational settings, including English language teaching. English for Pharmacist courses aim to equip pharmacy students with the necessary language skills to communicate effectively in professional settings in pharmacy. This study aimed to determine the implementation of Edpuzzle in teaching English to Pharmacists at ITEKES Bali. This study employed a qualitative research design. The sampling technique used was total sampling. Data were collected using a questionnaire and analyzed qualitatively. The findings revealed that implementing Edpuzzle in English for Pharmacist courses at ITEKES Bali effectively enhanced students' comprehension of English and left a good impression of using it. Edpuzzle enabled the instructors to track student engagement and progress, providing valuable data to inform their teaching approach. Moreover, Its features encouraged the students to stay focused and engaged with the course content, leading to better learning outcomes. The suggestions for the Edpuzzle video include adding more questions and increasing their difficulty levels to ensure attentive viewing. In conclusion, using Edpuzzle has positively impacted the learning process of English for Pharmacist courses at ITEKES Bali, improving students' understanding and engagement with the course materials. Edpuzzle can be an effective tool in teaching English for Specific Purposes, particularly in the context of English for Pharmacists.